الحماية الخاصة للأطفال أثناء النزاعات المسلحة - العيد، الراعي Aleid, Alraei (جامعة غرداية, 2017)
إيماناً منا بأن الطفل هو جوهر الحياة، وأساس بقائها هو شعوره بالأمن والسلام وضمان حريته واحترام كرامته في كل وقت، وعلى هذا الأساس تمت كتابة هذه الدراسة للبحث والوقوف على أهمية الحماية القانونية الخاصة للطفل في النزاعات المسلحة سواء الدولية أو الداخلية، فألزم القانون الدولي الإنساني الأطراف المتعادية بحماية الأطفال سواء كانوا مدنين أو مقاتلين، بإغاثتهم، وجمعهم مع أسرهم، ونقلهم من الأماكن المحاصرة، أما إذا شاركوا في الأعمال القتالية فإنهم يستفيدون من الحماية الخاصة سواء كانوا أسرى حرب أو لم يكونوا.
Our belief that the child is the essence of life and the basis of its survival is to make him feel secure and safe and to ensure his freedom and to respect his dignity all the time. On this basis this study had been written to search and stand on the importance of children's legal protection in both international armed conflicts and civil ones, so the international humanitarian law obliges the hostile parties to protect the children whether they were civilians or fighters by rescuing them, and meeting them with their families, and moving them from besieged places. In case that they participated in hostile actions, they benefit from special protection whether they were war prisoners or not.
Keywords: الأمن الوطني -- حقوق الطفل -- النزاعات المسلحة -- القانون الدولي